2015
DOI: 10.1021/ja512573q
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Enamine-Activation of Cyclopropanes for Highly Stereoselective Formation of Cyclobutanes

Abstract: A novel organocatalytic activation mode of cyclopropanes is presented. The reaction concept is based on a design in which a reactive donor-acceptor cyclopropane intermediate is generated by in situ condensation of cyclopropylacetaldehydes with an aminocatalyst. The mechanism of this enamine-based activation of cyclopropylacetaldehydes is investigated by the application of a combined computational and experimental approach. The activation can be traced to a favorable orbital interaction between the π-orbital of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 120 publications
(49 citation statements)
references
References 108 publications
0
43
0
4
Order By: Relevance
“…Recently,c yclopropyl activation by aH OMO-raising enamine strategy was demonstrated (Scheme 17). [84] It was shown that diphenylprolinol silyl ether 1a is able to open acetaldehyde cyclopropanes and facilitate the stereoselective formation of spirocyclobutaneoxindoles.T he observed g,breactivity pattern was not predicted. Reaction over the b,dpositions in a[ 3 + +2] cycloaddition had been anticipated as breaking of the cyclopropane bond would lead to reactive sites at these positions.H owever,i nstead of the expected cyclopentane structures,c yclobutanes were formed, possibly through a[ 2 + +2] cycloaddition involving ad ienamine intermediate.…”
Section: "Unexpected Developments"mentioning
confidence: 99%
“…Recently,c yclopropyl activation by aH OMO-raising enamine strategy was demonstrated (Scheme 17). [84] It was shown that diphenylprolinol silyl ether 1a is able to open acetaldehyde cyclopropanes and facilitate the stereoselective formation of spirocyclobutaneoxindoles.T he observed g,breactivity pattern was not predicted. Reaction over the b,dpositions in a[ 3 + +2] cycloaddition had been anticipated as breaking of the cyclopropane bond would lead to reactive sites at these positions.H owever,i nstead of the expected cyclopentane structures,c yclobutanes were formed, possibly through a[ 2 + +2] cycloaddition involving ad ienamine intermediate.…”
Section: "Unexpected Developments"mentioning
confidence: 99%
“…[48] Thep rocess functions well to yield the Very recently,Jørgensen and co-workers reported astrategy to access the spiro-cyclobutyl oxindole core (Scheme 23). [49] It was demonstrated that treatment of the b-cyclopropyl aldehyde 154 with 153 in the presence of 131 and PhCO 2 Hl ed to formation of the highly substituted cyclobutane 155.T hese reactions were proposed to proceed by catalyst-induced fragmentation of 154 to provide the dienamine 159.…”
Section: Enamine Catalysismentioning
confidence: 99%
“…Vorkurzem wurde die Cyclopropylaktivierung durch eine HOMO-Anhebung über Enamine beschrieben (Schema 17). [84] . .…”
Section: "Unerwartete Entwicklungen"unclassified